An Efficient Pattern Design Method for Plush Toys Using Component-Based Templates. (November 2020) - Jin, Yinghan; Feng, Wanting; Zeng, Long; Zhang, Dongliang
Abstract: In pattern design of a 3D plush toy model, the key task is to draw seam lines on the 3D surface to divide it into surface patches to obtain 2D patterns. However, how to draw seam lines requires a lot of professional knowledge and skills of pattern design. In this paper, we present a new method that can guide and assist users to create 2D patterns of a 3D toy model efficiently. Based on a component-based modeling method, we build a template library including the information of 3D components and seam lines. To design patterns of a toy, firstly, the most similar template will be retrieved from the library, then seam lines will be generated on the 3D surface automatically by mapping the template. Finally, 2D patterns will be obtained using a flattening method. The proposed method is easy-to-lean and easy-to-use, and it does not require the user to have much experience of pattern design. It can improve the efficiency of design and shorten the learning time for new designers and non-professionals. Highlights: A novel method is presented to aid users to create 2D patterns of toys efficiently. The component-based template is used for reusing knowledge of pattern design. Design information is mapped from the template which is retrieved from the library.